The Effect of Zone, Gender, RAE and Fitness Variables Towards Fitness Status and Anthropometric Attributes of Children in Malaysia - Abdullah, Prof. Madya Dr. Mohamad Razali; Juahir, Prof. Dr. Hafizan (Springer, 2020)
This research aims to identify the influence of zone, gender, RAE, and fitness performance variables and their relationship with physical fitness and anthropometric attributes of Malaysian children. Data were obtained from participants aged years old in Malaysia. The participants completed the multiple of test (anthropometrics, standing broad jump, twenty-meter speed, sit and reach and hand wall toss). Data interpretation was carried out using analysis of variance as well as principal component analysis (PCA). The PCA was computed to determine the appropriate components with an eigenvalue greater than (eigenvalue > .). Further analysis performed with varimax rotation demonstrated that some domain variables are able to distinguish children performances. The finding indicates that high performance children are attributed to considerable higher anthropometry and are lacking in flexibility as well as leg and hand strength amongst other variables (p < .). The overall findings revealed that zone, gender, RAE, fitness, and anthropometry do have an influenced toward children physical fitness performance in Malaysia. © , Springer Nature Singapore Pte Ltd.